Serbia: Tax Policy as Part of National Economic Governance - Popović, Dušan V. (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter analyses three specific characteristics of Serbian tax law and policy: tax competition, the prohibition of discrimination, and the prohibition of the abuse of law. First, we analyse the extent to which the Serbian legislative and executive powers resort to tax competition. Tax competition, a form of regulatory competition, exists when governments reduce fiscal burdens to encourage the inflow of productive resources or discourage their exodus. Non-discrimination is one of the fundamental principles of international tax treaty law, which may be found in hundreds of bilateral double taxation treaties that are currently being applied globally. This principle is articulated in most tax treaties concluded by the Republic of Serbia. Finally, this chapter analyses the general anti-abuse rule, such as the one incorporated in the EU Anti-Tax Avoidance Directive, which is the ‘minimum standard’ and does not preclude the application of domestic or agreement-based provisions aimed at safeguarding a higher level of protection for domestic corporate tax bases. Notably, in the Serbian legal system, the prohibition of the abuse of law is not articulated as a general principle of tax law. Instead, the legislature introduced the principle of facticity. Both administrative and judicial case law related to the application of the principles of facticity are limited.Keywords: taxation, Serbia, European integrations, abuse of law, tax competition, principle of non-discrimination